Last tooth in the arch syndrome management by using triple tray technique - Lina Lina; Haryo Mustiko Dipoyono; Maria Theresia Esti Tjahjanti; Murti Indrastuti (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2017)
Inter occlusal record serves as a guide to copy the upper and lower jaw relationship of the oral cavity to the articulator. Proper inter occlusal record minimizes the adjustment time of fixed denture in the patient’s mouth, thus saves the working time and cost. The making of fixed unilateral dentures involving the posterior teeth as abutments is often difficult in term of placing the working model of the upper jaw and lower jaw in articulator with proper occlusion (last tooth in the arch syndrome), therefore it is necessary to use inter occlusal record. One method to produce precise and simple inter occlusal record is a triple tray technique. This report provided information about how to use triple tray technique to produce inter occlusalrecord in the preparation of fixed denture of a patient with last tooth in the arch syndrome. A 54 years old male patient came to Prof. Soedomo Dental Hospital, Yogyakarta, Indonesia for a treatment using a denture due to the extraction of 16, 14, 24, 25, 26, and 46. The management of this case was comprised of anamneses, clinical and radiographic examination, first stage preparation of abutment tooth on 45 and 47, triple tray try in on prepared teeth, adjustment of the size of gauze, materials bite registration positioning on the surface of the upper and lower triple tray, inter occlusal record with a triple tray technique on maximum inter cusp position, the excess of bite registration materials trimming, articulator mounting, laboratory processing, and the fixed bridge insertion. Furthermore, stage II and III tooth preparation were performed using the same procedure. Based on our work, the triple tray technique is a simple method to produce an accurate inter occlusal record on a patient with a last tooth in the arch syndrome. ABSTRAKInter occlusal record berfungsi sebagai catatan untuk memindahkan hubungan rahang atas dan bawah dari rongga mulut ke artikulator. Inter occlusal record yang tepat meminimalkan penyesuain gigi tiruan cekat dalam rongga mulut sehingga menghemat waktu perawatan dan biaya. Pembuatan gigi tiruan cekat unilateral yang melibatkan gigi paling posteriorsebagai gigi penyangga seringkali terhambat karena kesulitan penempatan model kerja rahang atas dan rahang bawah pada artikulator dengan oklusi yang tepat (last tooth in the arch syndrome) sehingga diperlukan inter occlusal record. Salah satu teknik inter occlusal record yang sederhana dan akurat adalah menggunakan triple tray technique. Laporankasus ini memberikan informasi mengenai penggunaan triple tray technique untuk menghasilkan inter occlusal record dalam pembuatan gigi tiruan cekat pada kasus last tooth in the arch syndrome. Pasien laki-laki 54 tahun datang ke RSGM Prof. Soedomo Yogyakarta, Indonesia untuk dibuatkan gigi tiruan karena gigi 16, 14, 24, 25, 26, dan 46 telahdiekstraksi. Penatalaksanaan yang dilakukan meliputi anamnesa, pemeriksaan klinis dan radiografi, preparasi gigi penyangga tahap pertama pada elemen 45 dan 47, try in triple tray pada gigi yang dipreparasi, penyesuaian ukuran kasa, peletakkan bahan bite registration di permukaan atas dan bawah triple tray, inter occlusal record dengan triple tray technique pada maximum inter cusp position, pengurangan kelebihan bahan bite registration, penanaman padaartikulator, pemrosesan di laboratorium, dan insersi gigi tiruan cekat. Selanjutnya, dilakukan preparasi gigi penyangga tahap II dan III dengan prosedur yang sama. Berdasarkan laporan kasus ini, triple tray technique merupakan teknik inter occlusal record yang sederhana dan akurat pada kasus last tooth in the arch syndrome.